Preliminary study of a non-invasive portable device for continuous monitoring of blood alcohol concentration - Seco, Inês (2019)
Alcohol is one of the main constituents of alcoholic beverages and, surely, is the oldest and most abused drug among those currently known. This substance is one of the most common causes of traffic accidents and these in turn have become, over the years, a public health issue. The target audience of this study are users that want to consciously drink alcoholic beverages and particularly professional drivers. This is the target audience since despite having greater experience and responsibility, their profession is the most affected by the consumption of alcohol, especially due to the fact they spend more hours driving than average drivers, increasing the likelihood of traffic accidents. This paper describes a portable non-invasive device for continuous monitoring of the concentration of alcohol in the blood. This device consists essentially of two primary components: an amperometric biosensor, which promotes, collects and analyzes a sample of sweat, and the data acquisition and processing system, which makes the acquisition and analog/digital conversion of the biodata and subsequent digital processing of the results. Sweat is promoted by applying the technique of iontophoresis. Measurements are performed every 5 minutes, allowing the user to know in real time and in any place, which is his alcohol level.